Co‐Transplantation of Endothelial Progenitor Cells and Mesenchymal Stem Cells Promote Neovascularization and Bone Regeneration. (12th July 2013) - Zigdon‐Giladi, Hadar; Bick, Tova; Lewinson, Dina; Machtei, Eli E.
Abstract Background Bone formation relies on sufficient blood supply and osteoprogenitor cells. Purpose The study aims to evaluate the influence of endothelial progenitor cells (EPCs) in combination with mesenchymal stem cells (MSCs) on early vascularization and intramembranous bone regeneration. Materials and Methods Vertical bone regeneration was tested in rat calvarium guided bone regeneration model. Gold domes were filled with a mixture of 5 × 105 osteogenic transformed MSC and 5 × 105 EPC (EPC/MSC) that were mixed with β‐tricalcium phosphate (βTCP) scaffold. Domes filled with βTCP alone served as control. Rats were sacrificed after 4 or 12 weeks. Histomorphometry was used to determine blood vessel (Bv) density, vertical bone height, and bone area in the regenerated tissue. Results At both time points, new augmented hard tissue filled the space under the dome, and Bv density was higher in the EPC/MSC transplanted group vs control. However, bone height and bone area were similar among the groups 4 weeks posttransplantation, but were doubled in the EPC/MSC transplanted group 12 weeks posttransplantation. Conclusions EPC/MSC transplantation increases Bv formation in the early stages of healing that precedes enhancement of extracortical bone regeneration in later stages.